2016
DOI: 10.1111/and.12674
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effects of Resveratrol against azoxymethane-induced testis injury in rats

Abstract: To evaluate the protective effects of Resveratrol (RES) on azoxymethane (AOM)-induced testicular damage using histopathology and biochemical analyses, 28 male rats were randomly divided into four groups. Groups were control, RES, AOM and ARES. At the end of the 7 weeks, following routine tissue processing procedure, testis sections were stained with haematoxylin-eosin and Masson's trichrome. The blood samples were taken for biochemical analysis of testosterone, total oxidative stress, total antioxidant status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…These results are similar to those of Abd Elazeem et al (22) who induced hypothyroidism in 10 rats with carbimazole at a dose of 0.05 mg/kg / day for successive 3 weeks by gastric tube and examined their parotid glands and stated that hypothyroid status caused extensive collagen fibers in between the lobules. This increase in the collagen fibers was explained by Kurus et al (23) who stated that oxidative stress in the testicular tissue promotes excess collagen fibers production. Mallory's trichrome staining of the PTU&LCtreated group showed that LC administration diminished the previous effect in the PTU treated group where the collagen fibers distribution was much less in the capsule.…”
Section: Zagazig University Medical Journalsmentioning
confidence: 80%
“…These results are similar to those of Abd Elazeem et al (22) who induced hypothyroidism in 10 rats with carbimazole at a dose of 0.05 mg/kg / day for successive 3 weeks by gastric tube and examined their parotid glands and stated that hypothyroid status caused extensive collagen fibers in between the lobules. This increase in the collagen fibers was explained by Kurus et al (23) who stated that oxidative stress in the testicular tissue promotes excess collagen fibers production. Mallory's trichrome staining of the PTU&LCtreated group showed that LC administration diminished the previous effect in the PTU treated group where the collagen fibers distribution was much less in the capsule.…”
Section: Zagazig University Medical Journalsmentioning
confidence: 80%
“…These results are similar to those of Abd Elazeem et al [23] who induced hypothyroidism in 10 rats with carbimazole at a dose of 0.05 mg/kg / day for successive 3 weeks by gastric tube and examined their parotid glands and stated that hypothyroid status caused extensive collagen fibers in between the lobules. This increase in the collagen fibers was explained by Kurus et al [24] who stated that oxidative stress in the testicular tissue promotes excess collagen fibers production.…”
Section: Discussionmentioning
confidence: 80%